2009
DOI: 10.2967/jnumed.108.057455
|View full text |Cite
|
Sign up to set email alerts
|

Qualification of PET Scanners for Use in Multicenter Cancer Clinical Trials: The American College of Radiology Imaging Network Experience

Abstract: The PET Core Laboratory of the American College of Radiology Imaging Network (ACRIN) qualifies sites to participate in multicenter research trials by quantitatively reviewing submitted PET scans of uniform cylinders to verify the accuracy of scanner standardized uptake value (SUV) calibration and qualitatively reviewing clinical PET images from each site. To date, cylinder and patient data from 169 PET scanners have been reviewed, and 146 have been qualified. Methods: Each site is required to submit data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 5 publications
4
69
1
Order By: Relevance
“…This criterion 610% permissible variability is consistent with criteria of most other organizations that are currently addressing limits for acceptable quantitative PET scanner calibration performance for clinical trials (2,(13)(14)(15)18). Because spheres of different sizes are placed within the phantom in different background settings, and scanner-specific performance in this complex environment was originally unknown, rigid sphere-specific acceptance criteria for SUV max for the various sphere sizes are currently not strictly set.…”
Section: Phantom Imaging and Data Collectionsupporting
confidence: 60%
See 2 more Smart Citations
“…This criterion 610% permissible variability is consistent with criteria of most other organizations that are currently addressing limits for acceptable quantitative PET scanner calibration performance for clinical trials (2,(13)(14)(15)18). Because spheres of different sizes are placed within the phantom in different background settings, and scanner-specific performance in this complex environment was originally unknown, rigid sphere-specific acceptance criteria for SUV max for the various sphere sizes are currently not strictly set.…”
Section: Phantom Imaging and Data Collectionsupporting
confidence: 60%
“…These differences are not evident in the more common ACRIN-style cylindric phantom test of scanner uniformity. ACRIN's own observation of differences in mean liver SUV between vendors supports the existence of this problem (13).…”
Section: Scanner Calibrationmentioning
confidence: 63%
See 1 more Smart Citation
“…This discrepancy may be due to several factors: First, it may be a consequence of systematic differences in the technologic specifications and data-processing algorithms of the 2 scanners. Previous studies have shown that SUV measurements may not be highly reproducible across different scanner types or even between sites using the same scanners (32,38). The obvious differences in SUV reported in these previous studies have been observed despite the fact that phantom or patient data acquired under identical conditions have been used to test the reproducibility of the SUV.…”
Section: Discussioncontrasting
confidence: 41%
“…The spheres and the background needed to be filled with 18 F, and due to the 110 min half-life of 18 F, the data acquisition had to be appropriately timed to the filling to attain the desired activity concentration, making it difficult to perform repeat experiments with the same background and target activity concentrations as has been shown in several investigations. [14][15][16] Kinahan et al previously performed a multicenter phantom investigation of accuracy 17 and precision 18 of instrumental factors affecting PET tracer uptake measurements. In that study, the phantom was sent to centers with good physics support to assure the appropriateness of the data acquisition and analysis.…”
Section: Discussionmentioning
confidence: 99%